An evaluation of Britain’s position in the European Union - Duman, Burcu (My University, 2005)
Genel olarak, İngilizler diğer AB üyesi ülkelerin vatandaşlarına göre, AB konusunda daha şüpheciler. Fakat bu AB karşıtlığı olarak algılanmamalı. Britanyalıların coğrafi ve kültürel anlamda kendilerini Avrupalı hissetmeleri mümkün, ama ekonomik ve politik anlamda AB'ye karşı olmaları da kabul edilebilir bir gerçek. Bu tez çalışmasında, İngiltere'deki AB karşıtlığının gelişimi ele alınacak. Çalışmanın asıl amacı; özellikle İngiltere'de ortaya çıkan AB karşıtlığının niçin ve nasıl oluştuğunu anlamak. İngiltere, AB tarihini biçimlendiren ekonomik ve politik bütünleşmelerin genellikle dışında kaldı. 2. Dünya Savaşı sonunda lider Avrupa ülkesi olmayı başarmış İngiltere, o dönemde uluslar üstü bir bütünleşmeye katılmak istemedi. Fakat 1960'dan sonra, bazı uluslar arası gelişmeler İngiltere'nin AB üyeliği için başvuruda bulunmasına neden oldu. Üyelik süreci boyunca, AB İngiliz hükümetler için her zaman önemli bir konu oldu, çünkü baştan beri yapılması gerekenler konusunda Brüksel'e odaklanmayı istemediler. İngilizlerin arzusu AB içindeki çıkarlarını korumaktı. Bu çerçevede İngiltere'de ortaya çıkan şüphecilik faaliyetlerinin neden ve sonuçları, tez içinde incelenecek. Generally, Britons are more eurosceptic than other EU nations. But, in that point Euroscepticism in Britain should not be confused with anti-Europeanism. For majority society of Britain; it is perfectly possible to feel as a European in a geographical and cultural sense, but also be oppose to the European Union on political and economic grounds with acceptable reasons. This thesis examines the development of opposition and skepticism to the European Union in Britain, especially after 1980. The main aim of this thesis is to understand how and why opposition to the EU has been emerged in Britain; but this study especially includes the development of Euroscepticism in England which is a main nation of the United Kingdom. Britain has often been peripheral to the economic and political integration that has characterized the EU history. Having been the leading European nation at the end of the Second World War, Britain chose not to participate in the development of supranational European integration. But after 1960, some international developments provided Britain to apply to join the Union. In the membership period, the EU has always become an important issue for the British governments, because they did not want to focus on the rules of Brussels. The desire of Britain was to protect its interest in the EU. Because of these, it can be said that Eurosceptic activities emerged in Britain. In this study, the reason of the EU opposition will be analyzed.
Keywords: Avrupa Birliği_İngiltere